2-D lossless FIR filter design using synthesis of the paraunitary transfer function matrix - Wawryn, Krzysztof (1952- ); Poczekajło, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
A synthesis method for designing two-dimensional lossless finite impulse response (FIR) filters for various digital signal processing tasks is proposed. The synthesis method is based on using a 2-D embedding approach to obtain the paraunitary transfer function matrix of the lossless FIR filter. The elements of the paraunitary transfer function matrix are the transfer function of a given lossy FIR structure and the transfer functions for its complementary structures.
Keywords: lossless system; paraunitary transfer function matrix; FIR filter; embedding method